Author’s word-creation as a source of increasing the word-stock of the modern Belarusian language - Charnabroukina, Natallia U. (Journal of the Belarusian State University. Philology, 2024)
Based on contemporary academic literature and Belarusian literary texts of the 20th century, the paper attempts to select occasional words that can be entered into the word-stock of the modern Belarusian language. The logic behind it is that such lexical items are actively used by either one or several authors, have been created using productive word-building patterns and have eventually lost the effect of novelty. This practice existed in the first half of the 20th century, when the word-stock of the Belarusian literary language was extensively replenished with authors’ neologisms. Furthermore, this practice is observed in other Slavic languages – Russian and Ukrainian. The Belarusian literary language is no exception, therefore occasional words may eventually become part of its word-stock.
Keywords: Belarusian literary language; neologism; occasional word; potential word; word-creation; productive word-building pattern; word-stock of the Belarusian literary language; lexical meaning